The Battle for Backdoors and Encryption Keys - Donald L. Buresh (Journal of Current Scientific Research, 2021)
This paper argues that the use of backdoors in software is inherently counterproductive and leads to invasion of privacy, either by federal or state governments or by intrusive hackers. The essay outlines encryption’s nature, pointing out that a software backdoor is a secret means of ignoring data authentication. Several examples of known backdoors known to terrorists, criminals, and governments alike are highlighted. Arguments in favor and opposing backdoors are provided, where the Apple Computer, Inc. v. FBI controversy is discussed. Finally, the balancing of harms test as proposed by John Stuart Mill is introduced, where the article concludes that when balancing the opposing positions, the scale tips toward data encryption because an innocent party would suffer the most harm from the existence of a software backdoor.
Keywords: Apple Computer